Safety and efficacy of a feed additive consisting of chromium propionate (KemTRACE™ Chromium) for all growing poultry species (Kemin Europa NV). (29th April 2021) - ; Bampidis, Vasileios; Azimonti, Giovanna; Bastos, Maria de Lourdes; Christensen, Henrik; Dusemund, Birgit; Fašmon Durjava, Mojca; Kouba, Maryline; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; et al.
Abstract: Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of chromium propionate (KemTRACE™ Chromium; KemTRACE‐Cr) as zootechnical feed additive for all growing poultry species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) Panel was assigned to this mandate. Based on two tolerance studies submitted, the Panel concluded that the additive is safe for chickens for fattening at the maximum recommended supplementation level of 0.4 mg Cr/kg feed from KemTRACE‐Cr, but a margin of safety cannot be established; this conclusion can be extended to chickens reared for laying/breeding, but cannot be extrapolated to other growing poultry species. The FEEDAP Panel considered that the use of KemTRACE‐Cr in animal nutrition at the proposed conditions of use is safe for the consumer. No concerns for users following any inhalation exposure during the handling of the additive are expected; the additive was shown to be corrosive to the eyes but not irritant to skin or a skin sensitiser. The use of KemTRACE‐Cr in animal nutrition according to the proposed conditions of use will not significantly alter the concentration in the receiving environmental compartments of concern; therefore, no safety concern is expected for the environment. Based on three efficacy studies, the FEEDAP Panel concluded that KemTRACE‐Cr has the potential to be efficacious as a zootechnical additive in chickens for fattening at the supplementation level of 0.4 mg Cr/kg feed; this conclusion could be extended to chickens reared for laying and chickens reared for breeding, and extrapolated to other poultry species for fattening and reared for laying/breeding.